Natural gas : an international perspective : proceedings of the Oxford Energy Seminar 1982-1985 - Mabro Robert; Oxford Institute for Energy Studies (New York : Oxford University Press, 1986)
This book is a compilation of seminar reports which was aimed to educate professionals on factors and forces which influence the operations of the energy markets and the behavior of policy makers and economics agents.
asm 23/01/2019
Loans
Keywords: Gas, Natural; Energy (Natural gas)